PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Annisa Mawardani Putri; Erna Widiastuty (Jurnal Riset Akuntansi, 2025)
This study aims to provide empirical evidence of the influence of corporate governance mechanisms on firm value. The population of the research comprises all companies listed on the Indonesian Institute for Corporate Governance (IICG) from 2016 to 2022. Purposive sampling was employed, resulting in a sample of 199 firm-year observations. The independent variable, corporate governance mechanisms, was measured using the Corporate Governance Perception Index (CGPI) score. The dependent variable, firm value, was measured using Tobin's Q and sales growth. Firm size, the control variable, was proxied by total assets. Hypothesis testing was performed using simple linear regression. The results indicate that corporate governance mechanisms have a positive and significant impact on firm value. These findings support agency theory, which posits that corporate governance mechanisms has a positive and significant reduce conflicts of interest between principals-agents.